Effects of combined extract of cocoa, coffee, green tea and garcinia on lipid profiles, glycaemic markers and inflammatory responses in hamsters - Chang, Chih-Wei (BMC Complement Altern Med, 2015)
BACKGROUND: Dyslipidaemia is highly associated with cardiovascular and cerebrovascular diseases, which have been ranked second and third place of leading causes of death in Taiwan. Some plant extracts have been proved effective against dyslipidaemia. However, the combination of plant extracts was rarely studied. The purpose of the present study is to understand the beneficial effects of a combined extract (comprising cocoa, coffee, green tea and garcinia; CCGG) on lipid profiles in serum, liver, and faeces as well as glycaemic markers and related proinflammatory cytokines by using an appropriate animal model, the golden Syrian hamster. METHODS: A total of 40 male hamsters were randomly assigned to five groups: (1) vehicle control, (2) high-cholesterol diet control, (3) high-cholesterol diet of 311 mg/kg/d of CCGG, (4) high-cholesterol diet of 622 mg/kg/d of CCGG and (5) high-cholesterol diet of 1555 mg/kg/d of CCGG. At the end of the experiment, blood, tissue and faecal samples were collected for further analysis. RESULTS: After 6 weeks of treatment, CCGG supplementation significantly reduced serum lipid content (triglycerides, total cholesterol and LDL-C) and hepatic lipid content (triglycerides and cholesterol) with dose-dependent effects. In addition, an increase in excretion of faecal lipids (bile acids) was observed after supplementation. Furthermore, the homeostasis model assessment of insulin resistance (HOMA-IR) index and serum proinflammatory cytokine levels (TNF-α and IL-6) involved in dyslipidaemia was markedly improved. In addition, by monitoring biochemical parameters as well as histopathology of major tissues, no toxicity was observed after the consumption of CCGG. CONCLUSION: Dietary CCGG supplementation may exert potential effects on ameliorating hyperlipidaemia, insulin resistance, liver steatosis and related inflammation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12906-015-0806-1) contains supplementary material, which is available to authorized users.